2017
DOI: 10.1634/theoncologist.2017-0063
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a School-Based Educational Program to Increase Breast Cancer Awareness and Promote Intergenerational Transmission of Knowledge in a Rural Mexican Community

Abstract: In limited-resource settings, education is a valuable tool for achieving early detection and downstaging of breast cancer. Unfortunately, rural women lack access to educational opportunities and information about breast cancer, which is a factor contributing to late diagnosis and treatment. In this study, we demonstrated that implementing a school-based breast cancer educational program for female adolescents in a rural Mexican community was feasible, acceptable, and increased their knowledge about breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
(21 reference statements)
1
19
0
1
Order By: Relevance
“…In addition, several studies have acknowledged the impact of religion on breast cancer control, and suggest incorporating a component of religion when developing health education programs [45,46]. Educational campaigns at schools similarly can easily recruit participants and the knowledge learned while young will follow a woman through her life arming her with the necessary tools to recognize suspicious symptoms and seek care sooner [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have acknowledged the impact of religion on breast cancer control, and suggest incorporating a component of religion when developing health education programs [45,46]. Educational campaigns at schools similarly can easily recruit participants and the knowledge learned while young will follow a woman through her life arming her with the necessary tools to recognize suspicious symptoms and seek care sooner [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have acknowledged the impact of religion on breast cancer control, and suggest incorporating a component of religion when developing health education programs (44,45). Educational campaigns at schools similarly can easily recruit participants and the knowledge learned while young will follow a woman through her life arming her with the necessary tools to recognize suspicious symptoms and seek care sooner (46).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that female undergraduate students had a high level of understanding and satisfaction regarding a health education program designed to improve HL. An earlier pilot study for women was considered feasible and acceptable if more than 75% reported being satisfied with its contents [ 23 ]. Using easy-to-understand electronic and printed materials can advance knowledge and understanding and lead to improved cancer screening rates [ 24 ].…”
Section: Main Textmentioning
confidence: 99%